2017
DOI: 10.1016/j.dadm.2017.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Changes in metabolic risk factors over 10 years and their associations with late‐life cognitive performance: The Multi‐Ethnic Study of Atherosclerosis

Abstract: BackgroundWe examined whether changes in metabolic factors over 10 years were associated with cognitive performance.MethodsParticipants from the Multi-Ethnic Study of Atherosclerosis were followed since baseline (2000–2002) with five clinical examinations. At exam 5 (2010–2012), they received a short cognitive battery (Cognitive Abilities Screening Instrument [CASI], Digit Symbol Coding [DSC], and Digit Span [DS]). We examined associations between baseline metabolic factors and their changes over time before c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…43 In the current study we found a similar association between glucose and dementia risk in APOE ε4 allele non-carriers only. Levels of insulin, glucose, and Homeostatic Model Assessment-Insulin Resistance were related to increased AD risks or lower cognitive function among APOE ε4-negative but not APOE ε4-positive subjects based on data from prospective cohort 5,44 and cross-sectional studies, 45 which were consistent with our findings.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…43 In the current study we found a similar association between glucose and dementia risk in APOE ε4 allele non-carriers only. Levels of insulin, glucose, and Homeostatic Model Assessment-Insulin Resistance were related to increased AD risks or lower cognitive function among APOE ε4-negative but not APOE ε4-positive subjects based on data from prospective cohort 5,44 and cross-sectional studies, 45 which were consistent with our findings.…”
Section: Discussionsupporting
confidence: 88%
“…19 APOE ε4 might lead to increased risk of AD through multiple mechanisms including interference with the clearance of amyloid beta (Aβ), crosstalk with Aβ, lipid and glucose metabolism, and inflammation, 19 many of which are the potential pathways through which LS7 or its components are linked with cognition or dementia. 5,[20][21][22] Only a few studies have investigated the associations between adherence to a healthy lifestyle clustering and risks of dementia by stratification of APOE ε4 status, [23][24][25] and the results were inconsistent, with both stronger 24 or weaker 23,25 associations found in APOE ε4 allele carriers than in non-carriers. To the best of our knowledge, no study has examined the effect modification of APOE ε4 carriage on the association between LS7 scores and dementia risk.…”
Section: Research In Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Some longitudinal studies have reported an increased risk of incident cognitive impairment 6–10 and progression of cognitive impairment to dementia 10–14 with diabetes, whereas others observed no such associations 15–21 . Furthermore, although there is evidence linking prediabetes to changes in cognitive function 22 and brain integrity, 23 few studies have addressed prediabetes in relation to cognitive impairment, and with conflicting results 13,16 . Moreover, beyond diabetes status, the impact of glycemic control level on the preclinical/prodromal phase of dementia (ie, cognitive impairment) has been scarcely examined.…”
Section: Introductionmentioning
confidence: 99%
“…Though some early reports found no relationship between blood pressure and cognitive functioning (13, 14); growing evidence supports an association between increased blood pressure and lower cognitive performance in older adults (15). Recent studies also suggest a link between elevated blood pressure and various biomarkers of increased plaque and tangle load (16).…”
Section: Introductionmentioning
confidence: 99%